Stability Analysis of FGCNT Beams with Imperfections - Kumar, Pranav; Kumar, Ajay (Engineering, Technology & Applied Science Research, 2023)
Functionally Graded Carbon Nanotube (FG CNT) reinforced curved beams are being used nowadays in different structural applications due to their properties although they have stability issues due to geometric imperfections that affect the load-bearing capacity of the beam and residual strength, hence a geometric imperfection is being introduced as a hollow trapezoidal layer is incorporated in the curved beam design to get better strength. Hence a new frictional endo-stratified thermal model is proposed to analyze the frictional effect between interface layers with the help of elastic and plastic deformation of the curved beam. Thus, analysis is done in ABAQUS using a finite element model to determine the stability due to frictional characteristics. The proposed design is giving better results than existing designs with higher specific gravity and tensile strength.